Seminar Industri Pembekalan Elektrik di Malaysia - Anon (Universiti Malaysia Perlis (UniMAP), 2013)
Seminar Industri Pembekalan Elektrik Malaysia organized by School of Electrical System Engineering with the collaboration of Tenaga Nasional Berhad on 31st May 2012 held at Auditorium Hall, Pauh Putra Library, Pauh Putra Campus, Universiti Malaysia Perlis (UniMAP,) Perlis, Malaysia.